Columbia and Her Sisters: Personifying the Civil War - Johnson, Allison M. (American Studies, 2016)
This essay examines the ubiquity of female personifications in the literature and visual culture of the Civil War in order to illustrate the significance of symbolic femininity to both sides of the conflict and to document the various ways in which these personifications were strategically deployed. Based on substantial archival research, this essay inserts Columbia, also known as Lady Liberty, and other female personifications of the Union and the Confederacy into the critical discussion and historical understanding of the way in which American writers and artists understood the stakes and consequences of the conflict.